Kebijakan Pemerintah Indonesia Dalam Menanggapi Isu Keamanan Nasional Di Era Pandemi COVID-19 - Rifdah Syifa Rabbani; Ida Susilowati; Nasywa Tsabita Amelia; Savira Maulida (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
COVID-19 was declared a national epidemic in March 2020, three months after this outbreak first appeared in Wuhan, China. The Covid-19 phenomenon has had an impact on socio-political instability in various countries and has become a threat to the country's socio-economic security, such as; poverty, health and education. The government's role is the main element in handling human security issues during the Covid-19 era. This study uses a qualitative method with a descriptive analytical type of research. Data collection techniques were carried out using the literature study method, namely through literature research from books, scientific journals, theses, and theses. The results of the study show that the government, through its role as state administrator, has issued several policies in dealing with the COVID-19 pandemic, including through several policies, including; closing schools and workplaces, limiting religious activities and limiting public activities in order to inhibit the spread of COVID-19 in Indonesia.